Morpometric study of Hungarian honey bee (Apis mellifera L.) colonies - Zakar, Erika; Zajácz, Edit; Rácz, Tímea; Oláh, János; Jávor, András; Kusza, Szilvia (Acta Agraria Debreceniensis, 2013)
The honey bees are essential for the pollination of agricultural plants. The Pannonian honey bee, Apis mellifera pannonica, is native to Hungary, only these subspecies are being bread in our country. The parameters have been separated the pannon and italian honey bee subspecies, the colour of tergit, the cubital index and proboscis length. The morphometric analisys is of special importance because this, on the one hand, shows correlation with honey bee production and on the other hand, the pure morphometric charactersitics is the basis of any potential honey bee export. Mitochondrial DNA and microsatellites are the common methods to define genetic diversity and the separation of subspecies.